European Union Democracy Promotion and its impact on Civil Society in Central Asia - Fiedler, Radosław (Przegląd Politologiczny, 2018)
After a period of relatively small activity in this region, in 2007, the European Union offered a strategy for Central Asia. This strategy addressed many issues, including democratic deficit and human rights violations. The main obstacles to the implementation of the strategy are autocratic tendencies and corruption, the influence of neighbors strongly leaning towards autocracy and the post-Soviet legacy. Additionally, the EU’s activity is overshadowed by the US and has minimal capacity for pursuing its own policy toward Central Asia. Another problem is the fact that after implementing this EU strategy toward Central Asia there are no new initiatives which contribute to more visible European activity in that region.